Política educacional no Baixo Tocantins: a organização do ensino no município de Abaetetuba-PA - RODRIGUES, Daniele Azevedo (2019)
It is important to highlight that this study aims to understand the dynamics of teaching organization of the municipality of Abaetetuba-Pa and to understand how the political and social articulations have been debating an effectively democratic proposal of ordering the educational system in the municipality of Baixo Tocantins. The methodological option of this study was of a qualitative approach, because it is believed that this type of research because it believes that this will allow a detailed investigation of the object of study. In addition, research methods were used to collect and analyze data, documents and the interview with the representatives of the Municipal Secretariat of Abaetetuba, Union of Workers in Education, Municipal Council of Education and the city hall. The research used several sources to understand the pathways of the creation of the education system, its construction, the social and economic context of this process and the relationship between the system and the educational plan; therefore it was based on the conceptions of different authors such as Diva Chaves Sarmento, Dermeval Saviani, Carlos Roberto Jamil Cury, Alexandre Cals, Antonio Chizzotti, among others. The results indicate that the municipality of Abaetetuba has an education system based on a partisan political culture, which directly influences the organization, planning and also some positions in the education sector. With this, there is a strong interference in educational policies, which causes obstacles for the municipality to provide effective policies aimed at quality in Baetetubense education.